1996
DOI: 10.1016/s0022-5223(96)70223-4
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative angiographic assessment of radial artery grafts used for coronary artery bypass grafting

Abstract: The results of this study demonstrate that the short-term patency rate of radial artery grafts is excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 10 publications
2
43
1
4
Order By: Relevance
“…Based on the perceived advantages from arterial revascularization, the RA was increasingly used in the 1990s, either as a separate graft or in composite grafts. 20,24,34,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Several angiographic observational studies have shown that the RA achieves excellent short-, mid-, and long-term patency when used as a conduit for revascularization (see Table 2). Patency rates exceed that of SV grafts at all time points and are comparable to those observed for other arterial conduits.…”
Section: Patency Rates Of Radial Artery Conduitsmentioning
confidence: 99%
“…Based on the perceived advantages from arterial revascularization, the RA was increasingly used in the 1990s, either as a separate graft or in composite grafts. 20,24,34,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Several angiographic observational studies have shown that the RA achieves excellent short-, mid-, and long-term patency when used as a conduit for revascularization (see Table 2). Patency rates exceed that of SV grafts at all time points and are comparable to those observed for other arterial conduits.…”
Section: Patency Rates Of Radial Artery Conduitsmentioning
confidence: 99%
“…RA is also used in coronary artery bypass surgery as an arterial conduit. High quality clinical and angiographic results has previously been reported by the most authors [1][2][3][4].…”
Section: Discussionmentioning
confidence: 67%
“…10,[55][56][57][58][59][60][61][62][63][64][65][66][67] Patency rates of the RA have exceeded those of SV grafts at all time points and are comparable to other arterial grafts. Many reports have shown better outcomes of the RA compared with the SV, 10,56,58,59,[63][64][65]67 though some reported similar long-term graft patency. 33,45,48,66 Only the Cleveland Clinic reported worse graft patency of the RA than the SV.…”
Section: Patency Of Ra Graftsmentioning
confidence: 99%